Functional postural-stabilization tests according to Dynamic Neuromuscular Stabilization approach: Proposal of novel examination protocol - Kobesova, Alena; Davidek, Pavel; Morris, Craig E; Andel, Ross; Maxwell, Michael; Oplatkova, Lenka; Safarova, Marcela; Kumagai, Kathy; Kolar, Pavel (Journal of bodywork and movement therapies, 2020)
This paper presents a set of eleven functional Dynamic Neuromuscular Stabilization (DNS) tests corresponding with specific infantile developmental stages, clarifying desired postural-locomotion patterns from a developmental perspective, while also describing frequently-observed disturbances of these patterns.
Keywords: lidé; lokomoce; Locomotion; Postural Balance; posturální rovnováha; Humans